Accumulation of dry mass and macronutrients by sourgrass plants - Carvalho,L.B. (2013)
The experiment was carried out aiming to analyze the dry mass production and distribution and the content and accumulation of macronutrients in sourgrass (Digitaria insularis) plants cultivated under mineral nutrition standard conditions. Plants grew in 7-liter pots filled with sand substrate and daily irrigated with nutrient solution, being maintained under greenhouse conditions. Treatments consisted of times of evaluation (21, 35, 49, 63, 77, 91, 105, 119, and 133 days after emergence - DAE) and were arranged in a completely randomized design with four replicates. Sourgrass showed small accumulation of dry mass (0.3 g per plant) and macronutrients (3.7 mg of N per plant, 0.4 mg of P per plant, 5.6 mg of K per plant, 0.9 mg of Ca per plant, 0.7 mg of Mg per plant, and 0.3 mg of S per plant) at vegetative growth stage (< 49 DAE). Those accumulations increased mainly after 77 DAE, reaching the maximum theoretical value at 143, 135, 141, 129, 125, 120, and 128 DAE, for dry mass (12.4 g per plant), N (163.2 mg per plant), P (27.1 mg per plant), K (260.5 mg per plant), Ca (47.6 mg per plant), Mg (30.9 mg per plant), and S (13.7 mg per plant), respectively. K and N were found with higher rates and, as a consequence, they were required and accumulated in greater amounts in plant tissues of sourgrass.